2000
DOI: 10.1152/ajpendo.2000.279.5.e1131
|View full text |Cite
|
Sign up to set email alerts
|

Isoform-specific regulation of the lactate transporters MCT1 and MCT4 by contractile activity

Abstract: We examined the isoform-specific regulation of monocarboxylate transporter (MCT)1 and MCT4 expression by contractile activity in red and white tibialis anterior muscles. After 1 and 3 wk of chronic muscle stimulation (24 h/day), MCT1 protein expression was increased in the red muscles (+78%, P < 0.05). In the white muscles, MCT1 was increased after 1 wk (+191%) and then was decreased after 3 wk. In the red muscle, MCT1 mRNA accumulation was increased only after 3 wk (+21%; P < 0.05). In the white muscle, MCT1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

19
129
3

Year Published

2003
2003
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(151 citation statements)
references
References 49 publications
19
129
3
Order By: Relevance
“…5 ' 6 In humans, expression of MCTl may correlates with lactate removal 7 ' 8 and with the amount of lactate oxidised into muscle cells. 9 In humans, defects in MCTl transporter have been associated with several pathologies. Symptoms and signs of muscle injury on exercise and heat exposure plus subnormal erythrocyte lactate transport have been related with the presence of two mutations in the gene that codifies MCTl.…”
Section: Introductionmentioning
confidence: 99%
“…5 ' 6 In humans, expression of MCTl may correlates with lactate removal 7 ' 8 and with the amount of lactate oxidised into muscle cells. 9 In humans, defects in MCTl transporter have been associated with several pathologies. Symptoms and signs of muscle injury on exercise and heat exposure plus subnormal erythrocyte lactate transport have been related with the presence of two mutations in the gene that codifies MCTl.…”
Section: Introductionmentioning
confidence: 99%
“…MCT facilitates lactate transport across the plasma membrane. Endurance exercise training increases MCT1 expression, which facilitates lactate uptake into muscle cells (16). Endurance training also increases muscle glycogen concentration, but it remains unknown whether increases in MCT1 protein expression are associated with glycogen concentration after training.…”
mentioning
confidence: 99%
“…Numerous studies have shown that lactate transport and MCT expression in muscle could be regulated by physical activity and electrical stimulation in nonpathological states (3,9). Recently it has been shown that caloric restriction could also affect lactate transport activity in rats (20).…”
mentioning
confidence: 99%